2008
DOI: 10.1080/09540260801994649
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to address mental health through schools with examples from China

Abstract: The World Health Organization estimates that approximately one in five young people under the age of 18 experiences some form of developmental, emotional or behavioural problem, and one in eight experiences a mental disorder. Because research shows that half of adult mental disorders begin before the age of 14 and that early intervention can prevent and reduce more serious consequences later in life, it is critical to expand the role of mental health professionals with schools worldwide. Schools have the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Recently, there has been an emerging trend that moves beyond a problem-focused approach to embrace a more positive view of mental health (Morrison and Kirby, 2010). Fostering an inclusive and supportive social and physical environment can help to support the overall mental and emotional wellbeing of students (Whitman et al, 2008), but there is limited research that has explored how to navigate implementation of a positive mental health approach in schools. Since fostering a positive mental health approach contributes to psychological wellness and increased readiness to pursue goals related to healthy lifestyle change (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been an emerging trend that moves beyond a problem-focused approach to embrace a more positive view of mental health (Morrison and Kirby, 2010). Fostering an inclusive and supportive social and physical environment can help to support the overall mental and emotional wellbeing of students (Whitman et al, 2008), but there is limited research that has explored how to navigate implementation of a positive mental health approach in schools. Since fostering a positive mental health approach contributes to psychological wellness and increased readiness to pursue goals related to healthy lifestyle change (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of mental health issues has been growing within schools, and many schools now incorporate into their curriculum education about good mental health (Neil & Christensen, 2007;Whitman, Vince, Aldinger, Zhang, & Magner, 2008). This has occurred as a result of the increasing prevalence of mental health problems in children and adolescents, particularly anxiety and depression.…”
mentioning
confidence: 99%
“…Because China has implemented a nine-year compulsory education program for all school aged children, primary schools have become important functional entity for advocating and improving child mental health and the ideal place to provide related services. Research has shown programs promoting mental health are among the most effective of health promoting school efforts [ 77 ]. The mental health law mandates that all levels of school be equipped with psychologists and counseling teachers for mental disorders and psychological problems.…”
Section: Current State Of Chinese Child and Adolescent Psychiatry: Chmentioning
confidence: 99%